Case report: Microcirculatory leukocytes in a pediatric patient with severe SARS-CoV-2 pneumonia. Findings of leukocytes trafficking beyond the lungs - Bottari, Gabriella; Ince, Can; Confalone, Valerio; Perdichizzi, Salvatore; Casamento Tumeo, Chiara; Nunziata, Joseph; Bernardi, Stefania; Calò Carducci, Francesca; Lancella, Laura; Bernaschi, Paola; Russo, Cristina; Perno, Carlo Federico; et al. (Frontiers in Pediatrics, 2022)
Background SARS-CoV-2 can lead to excessive coagulation and thrombo-inflammation with deposition of microthrombi and microvascular dysfunction. Several studies in human and animal models have already evidenced biomarkers of endothelial injury during SARS-CoV-2 infection. Real-time observation of sublingual microcirculation using an handheld vital microscopy with an Incident Dark Field (IDF) technique could represent a non-invasive way to assess early signs of microvascular dysfunction and endothelial inflammation in patients with severe COVID-19 infection. Clinical case We report for the first time in a pediatric patient with severe SARS-CoV-2 pneumonia findings about microcirculatory leukocytes in the sublingual microcirculation of a 7 month-old patient admitted to our PICU using handheld vital microscopy with IDF technique. Results Sublingual microcirculation analysis revealed the presence of microcirculatory alterations and an extensive presence of leukocytes in the patient’s sublingual microcirculation. It’s significant to underline how the patient didn’t show a contextual significant increase in inflammatory biomarkers or other clinical signs related to an inflammatory response, beyond the presence of severe hypoxic respiratory failure. Conclusion Leukocyte activation in multiple organs can occur at the endothelial lining of the microvasculature where a surge of pro-inflammatory mediators can result in accumulation of activated leukocytes and degradation of the endothelium. The introduction of a method to assess in a non-invasive, real-time manner the extent of inflammation in a patient with COVID19 could lead to potential clinical and therapeutic implications. However, more studies are required to prove that studying leukocytes microcirculation using sublingual microcirculation analysis could be useful as a bedside point of care monitor to predict the presence of systemic inflammation associated with the impact of COVID-19, leading in a late phase of severe SARS-CoV-2 infection to a microvascular dysfunction and micro-thrombosis.